In pursuit of job satisfaction and happiness: Testing the interactive contribution of emotion-regulation ability and workplace social support. - Mérida-López, Sergio; Extremera-Pacheco, Natalio; Quintana-Orts, Cirenia Luz; Rey-Peña, Lourdes (My University, 2019)
The present study focuses on the interplay of emotion-regulation ability and perceived workplace social support as predictors of job satisfaction and happiness in a Spanish multi-occupational sample. A total of 494 working adults (39.4% females) took part in this study. Emotion-regulation ability and perceived support from colleagues and supervisors were positively associated. In addition, emotion-regulation ability and perceived support from colleagues and supervisors showed positive associations with job satisfaction and happiness. Furthermore, considering results from moderation analyses, when low levels of perceived workplace social support were reported, the relationship between emotion regulation and both job satisfaction and happiness was stronger than in cases of higher perceived workplace support. In line with previous studies, these findings suggest that training in emotion regulation abilities may take into consideration the potential moderating role of job characteristics such as support from colleagues and supervisors. Finally, theoretical and practical implications of the joint study of these factors in line with the Job Demands-Resources model and the Emotional Intelligence framework are discussed
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/3792
Keywords: Inteligencia emocional; Calidad de vida en el trabajo; Emotion-regulation ability; Workplace social support; Job satisfaction; Happiness; Interaction